2013
DOI: 10.2478/s11532-013-0314-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mechanical activation on structure and photocatalytic properties of ZnO powders

Abstract: Zinc oxide (ZnO) was mechanically activated in air using a planetary ball mill using varying milling speeds and time. The obtained samples were analyzed by X-ray diffraction analysis (XRD), scanning electron microscopy (SEM) and UV-Vis diffusion reflectance spectroscopy. The photocatalytic activity of the mechanically treated ZnO powders were investigated in the reaction of Malachite Green (MG) degradation in aqueous solution under UV-light irradiation. A decrease in the crystallite size (from 90 to 10 nm) acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The calculated crystallite size for samples S1 (∼80 nm), S2 (∼37 nm), and S3 (∼70 nm), are in concordance with previously reported values, which is generally reported between 10 nm and 100 nm, depending on the temperature and the synthesis conditions of the system. 51 Ghosh et al 52 found the existance of a trend of the crystallites to decrease in size when the strain increases. This may be due to the retarded crystal growth by the stretched lattice that increases the lattice energy and diminishes the driving force of the growth.…”
Section: Resultsmentioning
confidence: 99%
“…The calculated crystallite size for samples S1 (∼80 nm), S2 (∼37 nm), and S3 (∼70 nm), are in concordance with previously reported values, which is generally reported between 10 nm and 100 nm, depending on the temperature and the synthesis conditions of the system. 51 Ghosh et al 52 found the existance of a trend of the crystallites to decrease in size when the strain increases. This may be due to the retarded crystal growth by the stretched lattice that increases the lattice energy and diminishes the driving force of the growth.…”
Section: Resultsmentioning
confidence: 99%
“…For example, TiO 2 nanotubes functionalized with CuS quantum dots [76], nanosized hybrids of TiO 2 /SiO 2 [77], Sndoped TiO 2 nanostructured thin flms [78,79], bidoped TiO 2 -ZrO 2 ferromagnetic nanocomposites [80], and Ni x : TiO 2 thin flms [81]. ZnO or ZnSis another category of photocatalyst that has been applied in the photodegradation process of MG. As the same to TiO 2 , it has been used alone in the form of quantum dots [82], thin flms [83], nanoparticles [84] and powders [85], or prepared into composites such as Pt-doped ZnO [86], Mn-doped ZnS [84], Fe 3+ -doped ZnS [82], and a hybrid of ZnO nanorods grown on 3D reduced graphene oxide/Ni foam [87]. Novel photocatalysts are constantly being synthesized and successfully applied for the photodegradation of MG, which illustrates the great interest of researchers in such a category of AOPs.…”
Section: Degradation Of Mg In the Aquaculturementioning
confidence: 99%
“…Salah et al (2011) (Salah et al, 2011) firstly applied HEBM through a planetary mill up to 50h for reducing the particle size of ZnO to nanometric scale from a microcrystalline powder, suggesting the modifications induced in ZnO nanoparticles might prove useful as antibacterial material. Gancheva et al (2013) (Gancheva, Iordanova, Dimitriev, Avdeev, & Iliev, 2013) used the same milling to evaluate the photocatalytic activity of ZnO after milling for 10h with different milling speed rotation (Gancheva et al, 2013). Chen et al (2014) (D. Chen et al, 2014) stated that the defects promoted during HEBM highly influence the photocatalytic activity of ZnO with increased time and rotation due to the bulk defects promoted during the milling process.…”
Section: Introductionmentioning
confidence: 99%